Students’ Needs for TOEFL Preparation Course at University - Putri, Rahmi Eka; Syarif, Hermawati (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
This study aimed to identify students’ needs in the TOEFL Preparation course at university. This descriptive research was conducted on thirty first-semester students and the lecturer at Universitas Riau. The instruments were a needs analysis questionnaire for the students and an interview guideline for the lecturer. The results revealed that (1) Most of the students’ abilities were at the basic level; (2) Students took TOEFL Preparation course for several reasons such as to help them get a scholarship and as one of the requirements to finish their study; (3) Students preferred to learn through the teacher-centered method and doing more TOEFL exercises; (4) The lecturer should provide them various examples of TOEFL tests; and (5) The time for having TOEFL Preparation course needed to be extended. Overall, this research implied the need for a newly designed syllabus that could fulfil the students’ needs and could decrease their obstacles in learning TOEFL so that the students’ ability improved significantly.